1976
DOI: 10.1063/1.89039
|View full text |Cite
|
Sign up to set email alerts
|

Thermal reaction of Ti evaporated on GaAs

Abstract: The thermal reaction of a vacuum-evaporated Ti film with substrate GaAs has been investigated using Auger electron spectroscopy and x-ray diffractometry. As accumulation and Ga depletion at the Ti/GaAs interface and Ga pileup in front of the As-rich layer have been observed. The As-rich and the Ga-rich layers have been found to be composed of TiAs/Ti5As3 and Ti2Ga3/Ti5Ga4, respectively. It has also been found that the rate of the Ti-GaAs reaction is governed by the interdiffusion process of Ti and As at the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 7 publications
3
12
0
Order By: Relevance
“…From this observation, the layers B and C are suggested to be Ti-Ga and Ti-As, respectively. This is consistent with the previous results of electron diffraction analysis 7 and x-ray diffractometry, 8 which suggested that the layer formed above the original interface is Ti 2 Ga 3 or Ti x Ga 1Ϫx (xϭ0.35Ϯ0.05), and the lower layer is TiAs. At the point D, GaAs substrate, only Ga and As peaks are observed ͓Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…From this observation, the layers B and C are suggested to be Ti-Ga and Ti-As, respectively. This is consistent with the previous results of electron diffraction analysis 7 and x-ray diffractometry, 8 which suggested that the layer formed above the original interface is Ti 2 Ga 3 or Ti x Ga 1Ϫx (xϭ0.35Ϯ0.05), and the lower layer is TiAs. At the point D, GaAs substrate, only Ga and As peaks are observed ͓Fig.…”
Section: Resultssupporting
confidence: 92%
“…The activation energy of 1.74 eV is in good agreement with the previous results 7, 8 for the penetration of TiAs into GaAs at the temperature range of 400-550°C. But, it is not consistent with the activation energy obtained by the MTTF experiment at the temperature range of 300-350°C ͑Fig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations